KONSEP INSAN KAMIL MENURUT PEMIKIRAN ABDUL KARIM AL-JILI - Hasnawati, Hasnawati (Universitas Islam Negeri Imam Bonjol Padang, 2016)
This research aimed to examine the concept of insan kamil (perfect human) depend on Abdul karim Al-Jilli though.. The purpose of this study is to show the teaching of the insan kamil (perfect human concept). This study using descriptive kualitative methode, historical approach with library research technic. This descriptive type of research used document. Having analyzed the existing sample, writer concluded that al-Jilly description about insan kamil was the development from the concept written by Ibnu ‘Arabi, where it come from the concept of wihdatul wujud. Eventhough its still in line with islamic teaching and rule, because al-Jilli is still seperated between God and the creature.